Kepribadian Neuroticism dan Perilaku Menyimpang Pada Remaja Di SMK X Bekasi : Veggi Aini Citra, Yuarini Wahyu Pertiwi, Ditta Febrieta - Aini Citra, Veggi; Wahyu Pertiwi, Yuarini; Febrieta , Ditta (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
Deviation is related to the rules or laws apply where a person can't adjust to it, and finally results in a violation. Adolescents as individuals tend to have one of the personalities as the dominant factor for performing an action or behavior. Personal factors such as personality have the potential to shape deviant behavior. This is because personality is a characteristic of a person's thoughts, feelings and behavior that makes that person unique. Referring to The Big Five Personality theory, of the five dimensions there is one personality dimension, namely Neuroticism, which is defined as a personality with negative emotions so that it is prone to anxiety, depression, sadness, and aggression. The purpose of this study was to determine the relationship between neuroticism personality and deviant behavior in adolescents at SMK X Bekasi. The sampling technique used in this study was quota sampling with 120 respondents. The measuring instruments used are the neuroticism personality scale and the deviant behavior scale. The results of this study indicate the correlation coefficient value between the neuroticism personality variable and individual deviant behavior of 0.540**, group 0.479**, and mixed 0.461** with a significance level or sig(2-tailed) of 0.000 (p <0.05), so it can be stated that there is a relationship between neuroticism personality variables and deviant behavior in adolescents at SMK X Bekasi.